PENGARUH EXPERIENTIAL MARKETING TERHADAP SIKAP KONSUMEN MOTOR YAMAHA PADA PT LAKSANA KENCANA GEMILANG - Nursanti, Tinjung Desy; Melisa, Melisa (Binus Business Review, 2011)
Todayâs business competition is not just relying on product quality but further the quality of service. As the development of the era, marketers need an approach that combines the practice of non-traditional marketing that is integrated to enhance personal and emotional experience associated with the brand (experiential marketing). This corresponds closely with the customer experience and very different from the traditional marketing system that focuses on the functions and benefits of a product. This study is descriptive and causal. Descriptive study aims to determine consumer attitudes and causal research aims to influence experiential marketing on consumer attitudes on PT Laksana Yamaha Kencana Gemilang. Data was collected by distributing questionnaires and through literature study. Analysis of the data used in this research is Fishbein and regression models. The results showed that consumer attitudes Yamaha are positive and the influence of Experiential Marketing of consumer attitudes are significantly by 20.9%, while the remaining 79.1% influenced by other variables not examined in this study.Â